WLB And Job Satisfaction Changes During the Covid-19 Pandemic - Justyna PAWLAK (Communications of International Proceedings, 2021)
Sustainable social development depends, among others, on a reasonable work-life balance (WLB). This balance and the ways in which it can be maintained have been called into question by the changes associated with the Covid-19 pandemic. For some workers, these changes were clearly unfavourable, while others saw many advantages in them. The undertaken research examined the extent to which WLB perception, job satisfaction and the relationship between the two changed during the pandemic. A specially developed questionnaire, the MOAQ – JSS measure as well as interviews were used for this purpose. An analysis of the data obtained confirmed the hypothesis that for many people, during the pandemic the conditions affecting WLB changed and the relationship between WLB and job satisfaction became stronger. No significant correlation was found for gender or having children. In each group of respondents there were individuals satisfied with WLB changes as well as those who were more burdened by their responsibilities than before the pandemic. The obtained results may help to optimise ways in which professional duties are carried out, as some of the solutions introduced have proved to be mutually beneficial. They can also act as a guide in developing coping strategies in similar crisis situations.
Keywords: Work-Life Balance; Job Satisfaction; Social Sustainability; Covid-19; Pandemic